BRCA2 Heterozygosity Delays Cytokinesis in Primary Human Fibroblasts - Asta Björk Jonsdottir; Maaike P. G. Vreeswijk; Ron Wolterbeek; Peter Devilee; Hans J. Tanke; Jorunn E. Eyfjörd; Karoly Szuhai (Cellular Oncology)
Background: Inherited mutations in the tumour suppressor gene BRCA2 greatly increase the risk of developing breast, ovarian and other types of cancers. So far, most studies have focused on the role of BRCA-pathways in the maintenance of genomic stability.